Effect of Anogeissus leiocarpus leaf extract on blood glucose level in rats - abubakr, muzdalifa; Mahgoup, Mahgoup; Mohamed, Mohamed; Elmahdi, Elmahdi (Gezira Journal of Health Sciences, 2007)
The effect of the methanolic leaf extract of Anogeissus leiocarpus was studied in normal wister albino rats pretreated with a loading dose of glucose to explore its hypoglycaemic activity. Significant hypoglycemic effect was observed (P< 0.05) at a dose of 100 mg/kg B.W. 2 hours following treatment. At a dose of 200mg/Kg B.W. the plant extract showed no significant change in blood glucose level, while at a dose of 400mg/kg B.W. there was hyperglycaemic effect 2 and 4 hours following/after treatment.